1999
DOI: 10.1002/hep.510300317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vasopressin on portal-systemic collaterals in portal hypertensive rats: Role of nitric oxide and prostaglandin

Abstract: This study investigated the effect of vasopressin on portal-systemic collaterals in portal hypertensive rats and the influence of nitric oxide (NO) and prostaglandin on the responsiveness of collateral vessels to vasopressin. The vascular responsiveness to graded concentrations of vasopressin was tested with or without the incubation of n -nitro-L-arginine (NNA) (100 mol/L) and/or indomethacin (10 mol/L) in perfused collateral vascular beds of rats with portal hypertension induced by partial portal vein ligati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 32 publications
2
53
2
Order By: Relevance
“…37 Recently, prostaglandin was found to be involved in the modulation of collateral vascular tone in portal hypertensive rats and could modify the vasoconstrictive effect of vasopressin. 19 In this study, we found that incubation with indomethacin, NNA, or both significantly increased the collateral response to ET-1. These results suggest that both NO and prostaglandin are important factors involved in the attenuation of vascular response to ET-1 in portal-systemic collaterals.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…37 Recently, prostaglandin was found to be involved in the modulation of collateral vascular tone in portal hypertensive rats and could modify the vasoconstrictive effect of vasopressin. 19 In this study, we found that incubation with indomethacin, NNA, or both significantly increased the collateral response to ET-1. These results suggest that both NO and prostaglandin are important factors involved in the attenuation of vascular response to ET-1 in portal-systemic collaterals.…”
Section: Discussionsupporting
confidence: 49%
“…The in situ perfusion system was performed as described in previous reports. 18,19 Both jugular veins were cannulated with 16-gauge Teflon cannulas to ensure an adequate outflow without any resistance even at the highest flow rates. Heparin (200 /100 g body weight) was injected through one of the cannulas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors have previously demonstrated the vasoconstrictor effect of vasopressin, endothelin-1 (ET-1) and somatostatin on the collateral vessels in partial portal vein ligatedrats. [8][9][10][11][12] They also reported the vasoconstrictor action of ET-1 on the collaterals of bile duct-ligated cirrhotic rats. 13 The common triggering factor for both cirrhotic and noncirrhotic portal hypertension is an increased resistance to portal venous flow.…”
mentioning
confidence: 93%
“…Therefore, normalization of elevated portal pressure can be achieved by correcting the elevated portal resistance in the portal collateral circulation (the 'backward' hypothesis). 4,30 This is the basis of several experimental studies on the effects of different vasoactive substances and drugs on blood flow, the resistance to portal-systemic collaterals, [6][7][8][9][10][11][12][13][34][35][36][37] and their applications in the medical treatment of patients with cirrhosis. 32,38,39 If establishing the significance of alterations associated with portal hypertension could help to elucidate the mechanisms involved in its production and maintenance, we could, then, speculate on the hypothetical purpose of the splanchnic response in portal hypertension.…”
mentioning
confidence: 99%